Polarization correlometry of nets for characteristic states in Mueller-matrix patterns inherent to phase-inhomogeneous biological layers - Novakovs’ka, O.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Considered in this paper are the capabilities of the singular approach to the analysis of Stokes-parametric and Mueller-matrix patterns inherent to polycrystalline networks observed in phase-inhomogeneous biological layers. Offered is the model of nets for characteristic values of Mueller matrix elements that characterize mechanisms of formation of polarization singularities in laser images. The authors have grounded application of the method of cross-correlation two-point analysis aimed at polarization images formed by linear birefringence of biological crystal networks.